HIV Serostatus Disclosure and Its Predictors Among Children Living With HIV in Ethiopia: A Systematic Review and Meta-Analysis - Lemma, Tesfanesh; Silesh, Mulualem; Taye, Birhan Tsegaw; Desta, Kelem; Kitaw, Tebabere Moltot; Tekalign, Tiwabwork (Frontiers in Public Health, 2022)
Background HIV disclosure among children refers to when the caregiver is having disclosed to the child that he or she has HIV specifically. Disclosure significantly improved adherence to treatment and quality of life among children living with HIV/AIDS. Even though, the benefits of disclosure are considerable, informing a child of his or her own HIV status is often delayed. There is a dearth of studies on HIV serostatus disclosure among children in Ethiopia. Therefore, this study aimed to assess the pooled prevalence of HIV serostatus disclosure and associated factors among children living with HIV in Ethiopia. Methods and Materials Using a combination of search terms and Boolean operators, studies were retrieved from Pub Med/MEDLINE, EMBASE, CINAHL, Science Direct, Scopus, Web of Science, Cochran library, and Google Scholar. Five authors independently assessed the quality of each study using the modified Newcastle Ottawa Scale (NOS) for cross-sectional studies. STATA Version 11 software was used for statistical analyses. The random-effects (Der Simonian and Laird) method was used for the meta-analysis. The heterogeneity test was carried out with the help of I-squared (I2) statistics. A leave-one-out sensitivity analysis was carried out. Results A total of 12 articles with 3,410 participants were included in this systematic review and meta-analysis. The pooled prevalence of HIV serostatus disclosure among children was 36.87% (95% CI: 29.30, 44.44; I2 = 95.8%). Children aged older than 10 years (p = 0.003) and caregivers with primary and above education (p < 0.001) were factors significantly associated with HIV serostatus disclosure among children. Conclusions The finding of this study showed that HIV serostatus disclosure among children is relatively low. Therefore, developing clear guideline on HIV serostatus disclosure among children, strengthening public health education or community awareness creation about HIV/AIDS to promote the benefits of disclosure and extensively provision of counseling by health care providers are essential to enhance HIV serostatus disclosure among children. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021239035.